2006
DOI: 10.3928/01484834-20060501-09
|View full text |Cite
|
Sign up to set email alerts
|

The Kids Into Health Careers (KIHC) Initiative: Innovative Approaches to Help Solve the Nursing Shortage

Abstract: <h4>ABSTRACT</h4> <P>In 2001, the Northern Illinois University School of Nursing was awarded a grant from the Division of Nursing of the Bureau of Health Professions, Health Resources and Services Administration, U.S. Department of Health and Human Services, to enhance the School's advanced practice nursing program. As a recipient of this grant, the School of Nursing was required to incorporate activities to meet the goals of the "Kids Into Health Careers (KIHC) Initiative" to encourage child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“… 8 Another study in the nursing literature noted career development benefits through exposure within the K-12 (kindergarten through grade 12) educational setting 9 . Among the participants in this study, a majority of students indicated certainty regarding their career paths, which supports earlier investigations suggesting that career recruiting may need to take place prior to the student reaching high school 10 11 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“… 8 Another study in the nursing literature noted career development benefits through exposure within the K-12 (kindergarten through grade 12) educational setting 9 . Among the participants in this study, a majority of students indicated certainty regarding their career paths, which supports earlier investigations suggesting that career recruiting may need to take place prior to the student reaching high school 10 11 …”
Section: Discussionsupporting
confidence: 86%
“…9 Among the participants in this study, a majority of students indicated certainty regarding their career paths, which supports earlier investigations suggesting that career recruiting may need to take place prior to the student reaching high school. 10,11 Students in this study maintained a strong outlook on attending college, with the majority planning to attend a fouryear college. However, knowledge of college EMS programs was lacking, with many students unaware of AAS and BS programs for EMS.…”
Section: Discussionmentioning
confidence: 90%
“…Career fairs are another strategy to increase awareness of nursing in middle school students. The Northern Illinois University School of Nursing Rural Adult Nurse Practitioner Project initiated the Kids Into Health Careers project by teaming with school nurses (Cohen et al., 2006). Activities included participating in school health fairs, interacting with students, and playing games that highlighted the characteristics of a nurse, settings where they work, and education needed to become a nurse.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This question may receive an affirmative answer in the future after widespread implementation of recruitment. It will take time to determine if efforts such as the Kids Into Health Careers (KIHC) Initiative (Cohen et al, 2006), Career Awareness Recruiters and Educators (C.A.R.E.) Project (Kansas Schools of Nursing, n.d.), Nursing Exploration Summer Camp (Drenkard et al, 2002), Gaining Excellence in Nursing Education: Students Intensifying Scholarship (GENESIS) Project (University of Michigan School of Nursing, n.d.), The 2007 Middle School Scholars Program for Nursing and Health Careers (Pace University, 2006), and Prenursing Club: A Recruitment Program for Minority School-Age Children (Stearns & Marchione, 1989) will result in more students entering the nursing profession.…”
Section: Measuring the Effectiveness Of Interventionsmentioning
confidence: 99%